COVID-19 associated Invasive Fungal Rhinosinusitis: A Retrospective Analysis of 15 Cases. (March 2022) - Niyas, V.K. Muhammed; Arjun, R.; Felix, V.; Kumar, M.A. Suresh; Lalitha, S.
Abstract : Purpose: India is witnessing an increasing number of invasive fungal infections, especially mucormycosis, associated with the second wave of the COVID-19 pandemic. The purpose of this study is to describe the epidemiological and clinical features of patients with COVID-19 associated invasive fungal sinusitis (CIFRS) who presented to our centre (KIMSHEALTH, a tertiary hospital in Thiruvananthapuram, Kerala, India). Methods & Materials: We included biopsy and/or culture proven invasive fungal rhinosinusitis in patients who had history of COVID-19 infection (confirmed by RT-PCR or an antigen based test). Clinical details were collected by review of the electronic medical records and analysis was done by descriptive statistics. Results: 15 patients who satisfied the inclusion criteria were included in the analysis. This included 11 cases of rhino orbital mucormycosis, 2 cases of invasive aspergillosis and 2 cases of co-infection with Mucorales and Aspergillus species. Fungal culture showed growth of Mucorales in 4 patients and Aspergillus flavus in one patient. The mean age of the patients was 58.0 ± 9.7 years, and 12 were male. Type 2 diabetes mellitus was a common additional risk factor in all the patients and the mean HbA1c was 9.9 ± 2.1. All patients except two had received corticosteroids as a part of their COVID-19 treatment. All patients except one had used steam inhalation for symptom relief for COVID-19 symptoms. The median duration between the diagnosis of COVID-19 and the diagnosis of CIFRS was 20 days (interquartile range: 16-27). All patients underwent emergency endoscopic sinus debridement surgery followed by antifungal medicines. Antifungals used included liposomal amphotericin B, amphotericin B deoxycholate and isavuconazole for mucormycosis patients while two patients with invasive aspergillosis were treated with isavuconazole. At the time of reporting one patient had expired while the others have shown clinical improvement. Conclusion: The common risk factor for all cases of CIFRS was diabetes mellitus. Majority of patients also had history of steroid use and steam inhalation during their COVID-19 treatment. Their role in pathogenesis need to be ascertained by larger studies.